Penggunaan Metode Altman Z-Score Untuk Mengetahui Potensi Terjadinya Financial Distress (Studi Kasus Pada PT Bekasi Asri Pemula Tbk.) Periode Tahun 2019-2021 - Alma Tazkiah; Ananda Putri Yudhistira; Annas Rabbani; Nabila Nur Azizah (Universitas Kristen Indonesia Toraja, 2023)
This research aims to identify and analyze financial distress by using the Altman Z-Score methodology to predict the bankruptcy of property and real estate companies listed on the IDX based on the 2019 - 2021 period. The data were obtained from published financial reports by www.idx.coi.id with the period from 2019 to 2021. Research population is property and real estate companies registered with the IDX with a sample of annual financial report data for 3 consecutive years. Data collection techniques with literature study. The results of this research show that in 2019 - 2021 PT Bekasi Asri Pemula Tbk. is in the healthy zone. This is based on the Altman Z-Score criteria, if Z > 2.99 is categorized as a healthy company, if Z is between 1.81 to 2.99 it is categorized a grey area, and if Z < 1.81 it is categorized as the initial company went bankrupt.